Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021, Lingkup Pemerintah Kabupaten Maluku Tenggara - Cherie Delia Agnes Makisurat; Salmon Eliazer Marthen Nirahua; Sherlock Halmes Lekipiouw (Faculty of Law Universitas Pattimura, 2023)
The implementation of Civil Servant Discipline Enforcement regulated in PP Number 94 of 2021 and BKN Regulation Number 6 of 2022, is very clear so that it is hoped that every civil servant must try to understand these regulations, so that they can make it a guideline for how they should behave inside and outside the officialdom. In practice, what is desired or enforced is often far different from the reality. This research was conducted at the Government of Southeast Maluku Regency, BKPSDM Southeast Maluku Regency. This research was conducted with the aim of (1) Examining the implementation of the provisions of Article 15 Paragraph (2) of PP Number 94 of 2021 and analyzing what problems or factors affect the application of disciplinary enforcement sanctions. (2) To reveal and analyze the application of sanctions for violations of Article 11 paragraph (2) letter d Number 4, PP Number 94 of 2021 This research is empirical juridical research, or called field research, which examines the applicable legal provisions and what happens in reality in society. The results showed that: 1). The implementation of civil servant discipline related to Article 15 Paragraph (2) has been going well but not optimal, Article 15 Paragraph (2) is very clear but sometimes it is misunderstood, the application of sanctions by the head of the OPD is not the termination of salary payments but the practice that occurs is the blocking of salary accounts. 2). Article 11 Paragraph (2) letter d Number 4, a civil servant named SJ, Karel Sadsuitubun Hospital, Registrar Class Tkt.I, II / d did not carry out his duties continuously for three (3) years, PPK imposed severe punishment in the form of Honor Dismissal not at his own request. From the results of the research there were 4 cases of the same offense while in the process of summoning and examining the Discipline Enforcement Team, all of which came from RSUD Karel Sadsuitubun Langgur. 3).Problems faced, misapplication of sanctions and employee welfare affect the level of civil servant violations, meaning that if employee welfare is good then employee discipline increases, if welfare does not exist it can cause behavioral anomalies. Discipline must be balanced with employee welfare.